Hukum Investasi Saham Menurut DSN-MUI dan AAOIFI: Tinjauan Fikih Muamalah: Stock Investment Law According to DSN-MUI and AAOIFI: Review of Muamalah Fiqh - Muhammad Shiddiq Abdillah; Islahuddin Ramadhan Mubarak; Andi Khaula Al Hannan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research aims to determine the legal status of stock investment according to DSN-MUI and AAOIFI and to analyze their opinions from the perspective of Islamic jurisprudence (fiqh muamalah). This study employs a descriptive qualitative method through library research. The findings of the research are as follows. Firstly, DSN-MUI holds that investment in joint-stock companies with elements of usurious transactions is permissible under certain conditions and requirements. Secondly, AAOIFI also considers it permissible under specific conditions and requirements. Thirdly, based on the analysis of fiqh muamalah, the correct opinion is that trading in stocks is entirely prohibited if there are elements of usury or impermissibility within a company. Despite various considerations of fiqh principles, maslahat istishlahiy, and other rules, it remains prohibited because the prohibition of usury is clear in the Quran, which states that Allah permits trade and forbids usury. Based on the results of this research, it is advised for those who wish to invest in joint-stock companies to first investigate the company they are interested in. If there are usurious transactions within it, participation in the company is prohibited. However, if there are no usurious transactions, then participation in the company is allowed.